"Cheíta" Quintana… Something different (Mayéutica Revista Científica de Humanidades y Artes, 2023)
"Cheíta" Quintana was and will continue to be one of the most recognised and emblematic lyrical voices on the Venezuelan musical scene. Although her sphere of influence was national, she made her homeland her own, Lara state, Venezuela, to which she dedicated her whole life, becoming the identifying female voice. Not only singing, but also education, were the axes of her professional development, leaving a deep mark in the region.
Keywords: Cheíta Quintana; Lara state; singing; Divina Pastora; Universidad Centroccidental Lisandro Alvarado